Spontaneous formation of nanostructures during pulsed laser deposition of epitaxial half-Heusler TiNiSn on MgO(001) - R. W. H. Webster; J. E. Halpin; S. R. Popuri; J.-W. G. Bos; D. A. MacLaren (APL Materials, 2019)
The half-Heusler alloy TiNiSn is a promising material for thermoelectric applications that is inexpensive and non-toxic. We demonstrate the epitaxial growth of smooth TiNiSn thin films on MgO(001) single crystal substrates by pulsed laser deposition, using transmission electron microscopy to investigate nanoscale structural and chemical inhomogeneities. In particular, an interfacial reaction results in the formation of a titanium-rich oxide nanolayer at the substrate interface, and this maintains epitaxy but perturbs film composition. Segregation effects are observed throughout the film, producing a narrow range of off-stoichiometric, half-Heusler compositions. The propensity of titanium to oxidise also leads to the commensurate formation of parasitic titanium oxide nanostructures which may be overlooked in bulk techniques but are a key feature that drives both the formation of Ni-enriched, full-Heusler phases and the local decomposition of the half-Heusler to form additional nickel-stannide phases.